2021
DOI: 10.3389/fpls.2021.666066
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 Modulates Plant Hydraulic Conductance Through Regulation of PIPs Under Progressive Soil Drying in Tomato Plants

Abstract: Increasing atmospheric CO2 concentrations accompanied by abiotic stresses challenge food production worldwide. Elevated CO2 (e[CO2]) affects plant water relations via multiple mechanisms involving abscisic acid (ABA). Here, two tomato (Solanum lycopersicum) genotypes, Ailsa Craig (AC) and its ABA-deficient mutant (flacca), were used to investigate the responses of plant hydraulic conductance to e[CO2] and drought stress. Results showed that e[CO2] decreased transpiration rate (E) increased plant water use effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…In addition, e [CO 2 ] decreased g s in flacca despite the slight influence on SA , and these effects were absent in ABA-treated flacca . Although the retarded stomatal response to e [CO 2 ] in flacca was attributed to ABA deficit ( Wei et al, 2020 ; Li et al, 2021 ), exogenous ABA application could not recover the response due to its strongly induced stomatal closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, e [CO 2 ] decreased g s in flacca despite the slight influence on SA , and these effects were absent in ABA-treated flacca . Although the retarded stomatal response to e [CO 2 ] in flacca was attributed to ABA deficit ( Wei et al, 2020 ; Li et al, 2021 ), exogenous ABA application could not recover the response due to its strongly induced stomatal closure.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the higher stomatal density and greater stomatal size in flacca compared to the wild type under either well-watered or drought-stressed conditions ( Fang et al, 2019 ; Innes et al, 2021 ; Li and Liu, 2021 ), it is more vulnerable to adverse environments, including soil drought and high evaporative demand conditions. By using wild type tomato and flacca plants, Wei et al (2020) and Li et al (2021) found that e [CO 2 ] decreased g s , retarded stomatal drought response, and reduced hydraulic conductance in an ABA-dependent pathway. Namely, these effects were absent or attenuated in flacca plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the xylem sap ABA, earlier studies showed that under salt stress, the rapid synthesis of ABA in leaf also was a predominant factor controlling stomatal aperture (Li et al, 2021; Zhang et al, 2018). Consistent with this, we observed that salinity obviously induced the accumulation of ABA in leaf ([ABA leaf ] (Figure 5a).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increasing salinity stress, carbon dioxide (CO 2 ) concentration in the air is also considered to be one of the several important factors that have significantly affected natural and agricultural ecosystems (Bloom et al, 2012). The current atmospheric CO 2 concentration has surpassed 400 ppm, and according to predictions, CO 2 concentration will reach 800 ppm by the end of this century (Li et al, 2021). A number of previous literatures have indicated that elevated CO 2 ( e [CO 2 ]) could positively affect net photosynthetic rate ( A n ), growth and biomass of plants, and also influence the ratio of carbon (C) to nitrogen (N), as well as the concentrations of plant hormones (Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Two Tomato genotypes, one of them being a mutant deficient in ABA were tested for responses of hydraulic conductance at eCO2 by [23], they found that a reduction in the transpiration rate and a concomitant increase in the water use efficiency (WUE) was seen in the wild type and not in the mutant, clearly indicating a role of ABA in this response. On the other hand, both in the mutant and the wild type, increased water use and osmotic adjustment was seen, this shows us that plant water consumption which also includes water transpired is not entirely controlled by ABA.…”
Section: The Aba Conundrummentioning
confidence: 99%